Management of incidental gallbladder cancer in a national cohort. Issue 9 (1st July 2019) - Lundgren, L.; Muszynska, C.; Ros, A.; Persson, G.; Gimm, O.; Andersson, B.; Sandström, P.
Abstract : Background: Incidental gallbladder cancer is a rare event, and its prognosis is largely affected by the tumour stage and treatment. The aim of this study was to analyse the management, treatment and survival of patients with incidental gallbladder cancer in a national cohort over a decade. Methods: Patients were identified through the Swedish Registry of Gallstone Surgery (GallRiks). Data were cross‐linked to the national registry for liver surgery (SweLiv) and the Cancer Registry. Medical records were collected if registry data were missing. Survival was measured as disease‐specific survival. The study was divided into two intervals (2007–2011 and 2012–2016) to evaluate changes over time. Results: In total, 249 patients were identified with incidental gallbladder cancer, of whom 92 (36·9 per cent) underwent re‐resection with curative intent. For patients with pT2 and pT3 disease, median disease‐specific survival improved after re‐resection (12·4 versus 44·1 months for pT2, and 9·7 versus 23·0 months for pT3). Residual disease was present in 53 per cent of patients with pT2 tumours who underwent re‐resection; these patients had a median disease‐specific survival of 32·2 months, whereas the median was not reached in patients without residual disease. Median survival increased by 11 months for all patients between the early and late periods ( P = 0·030). Conclusion: Re‐resection of pT2 and pT3 incidental gallbladder cancer was associated with improved survival, but survival was impaired when residual disease was present. A higher re‐resection rate and more R0 resections in the later time period may have been associated with improved survival. Abstract : In this study, based on validated prospective registries, a 10‐year cohort of patients with incidental gallbladder cancer in Sweden were analysed regarding management, treatment and survival. Re‐resection in patients with pT2 and pT3 disease increased disease‐specific survival. Survival outcome also improved over the study period, which may have been due to an increased re‐resection rate and increased proportion of R0 resections. More re‐resections, better survival